Pemanfaatan Teknologi Untuk Implementasi Pendidikan Pancasila Dalam Penguatan Nilai Di Era Digital - Ikrom Bahari; Zihan Adin Fisabilillah; Anindya Nurshadrina Ramadhani; Deswita Diandra; Jasmine Nur Syamsina; Sabilillah Hadian; Yayang Furi Furnamasari (Pusat Riset dan Inovasi Nasional, 2024)
In the digital era, technological developments have changed the paradigm of education and teaching, including the implementation of Pancasila values. This article explores the role of technology in strengthening Pancasila values ​​in the digital era. Through the literature study method, this research collects and analyzes various literature sources relevant to this theme. The results show that the use of technology, especially in character education, can increase the accessibility, effectiveness and relevance of Pancasila values. Digital learning media allows students to learn independently and collaboratively, and facilitates the delivery of Pancasila values ​​more easily and interestingly. However, challenges also arise, including problems in implementing norms and ethics, as well as the negative impacts of technology use. Therefore, an effective strategy is needed to utilize technology wisely to strengthen the values ​​of Pancasila in the digital era.